A preparation process of permanent ferrite magnetic rotor

By adding rare earth elements to the preparation of permanent magnet ferrite magnetic rotors and adopting a segmented sintering process, the temperature stability and mechanical strength of the magnet are improved, and the problem of high residual magnetic temperature coefficient of permanent magnet ferrite in the prior art is solved, and more stable magnetic properties and longer service life are achieved.

CN119787744AInactive Publication Date: 2025-04-08HAIAN JULI MAGNETIC MATERIAL CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202510011578.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-04
Publication Date
2025-04-08
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The existing permanent magnet ferrite magnetic rotor preparation process is difficult to reduce the residual magnetic temperature coefficient of permanent magnet ferrite, resulting in poor temperature stability of the magnetic rotor.

Method used

By adding rare earth elements to the preparation and controlling the heating rate and insulation time using a segmented sintering process, the microstructure and magnetic domain structure of the magnet are improved. At the same time, epoxy resin material is used for surface treatment to form a protective film to improve mechanical strength.

Benefits of technology

It effectively improves the temperature stability and mechanical strength of the magnet, extends the service life of the rotor, and improves the overall performance of the magnetic rotor.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The present invention discloses a preparation process of a permanent ferrite magnetic rotor, and relates to the technical field of permanent ferrite magnetic rotor preparation, including raw material preparation, crushing treatment, molding process, sintering process, processing and magnetization, surface treatment and performance testing. The crushing process mixes large-grain raw materials together and grinds them into permanent ferrite magnetic powder. The molding process uses an injection molding method to press the powder into a rotor. The sintering process uses a segmented sintering process to perform high-temperature sintering treatment on the formed blank. The present invention adds rare earth elements in the preparation, and changes the microstructure and magnetocrystalline anisotropy of the magnet by doping modification, thereby improving the magnetic properties. The segmented sintering process can make the grain structure inside the material more dense and uniform, so that the magnetism of the magnetic rotor prepared subsequently will not change significantly due to temperature changes, and effectively improve the temperature stability of the magnet.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of permanent ferrite magnetic rotor preparation, in particular to a permanent ferrite magnetic rotor preparation process. Background Art

[0002] Permanent ferrite is made of SrO or BaO and ferric oxide through ceramic process. It is an important component of magnetic materials and is widely used in the electronics industry, information industry, motorcycles, power tools, automobile industry and other industries. Permanent ferrite materials are made into rotors, which can be used to generate magnetic fields in motors and other equipment and interact with stators. The existing preparation process makes it difficult to reduce the residual magnetism temperature coefficient of permanent ferrite, and thus it is difficult to improve the temperature stability of the rotor.

[0003] The defects of the existing permanent ferrite magnetic rotor preparation are: 1. Patent document CN111362681B discloses a high-performance permanent ferrite magnet sintered after injection molding and a preparation method thereof. The patent mainly considers how to improve the magnetic energy product of the permanent ferrite while maintaining the advantages of easy molding and multi-pole orientation of the injection-molded permanent ferrite magnet, but does not consider how to reduce the residual magnetization temperature coefficient of the permanent ferrite, so that the magnetism of the magnetic rotor prepared subsequently will not change significantly due to temperature changes, effectively improving the temperature stability of the magnet; 2. Patent document CN110149034B discloses a method for preparing a permanent magnet rotor assembly, which mainly considers how to prepare a permanent magnet rotor at a low cost, but does not consider how to improve the mechanical strength of the prepared permanent magnet ferrite magnetic rotor, thereby extending the service life of the rotor; 3. Patent document CN111471940B discloses a high-strength stainless steel rotor and a method for preparing the same. It mainly considers how to prepare a rotor with high strength and excellent fatigue resistance, but does not consider how to increase the magnetic energy product of the permanent ferrite and thus improve the magnetic properties of the final product. 4. The fracture toughness and impact strength of existing magnetic rotors are difficult to guarantee, which in turn affects the overall performance of the rotor. Summary of the invention

[0004] The object of the present invention is to provide a process for preparing a permanent ferrite magnetic rotor to solve the problems raised in the above background technology.

[0005] To achieve the above-mentioned purpose, the present invention provides the following technical solutions: a preparation process of a permanent ferrite magnetic rotor, including raw material preparation, crushing treatment, molding process, sintering process, processing and magnetization, surface treatment and performance testing, wherein the crushing process mixes large-particle raw materials together and grinds them into permanent ferrite magnetic powder, the molding process uses an injection molding method to press the powder into a rotor, the sintering process uses a segmented sintering process to perform high-temperature sintering treatment on the formed blank to form a permanent ferrite phase with stable magnetic properties, the processing and magnetization perform mechanical processing and magnetization on the sintered rotor, the surface treatment is used to coat a protective film on the surface of the magnetic rotor, and the performance test is performed according to the standard documents of GB / T12796.1-2012 and GB / T3217-2013 on the performance of the prepared permanent ferrite magnetic rotor to screen out products with unqualified quality; The raw materials include iron oxide, barium oxide, rare earth elements, silicon carbide fiber, titanium dioxide, silicon dioxide, calcium carbonate, plasticizer, lubricant and binder; The sintering process includes sintering pre-treatment, first stage sintering, second stage sintering, third stage sintering and cooling stages; Pre-sintering treatment: Check the green body of the formed magnetic rotor, remove the rotors with surface defects, and then put the qualified rotors into the sintering furnace, and introduce oxygen into the furnace in advance, with an atmosphere flow rate of 0.2-0.3L / min; The first stage of sintering: After 5-10 minutes, heat at a heating rate of 2-4℃ / min. When the temperature reaches 450-550℃, stop heating and keep warm for 40-80 minutes. Second stage sintering: then raise the temperature to 950-1050°C at a heating rate of 6-9°C / min, introduce hydrogen into the sintered steel sheet at an atmosphere flow rate of 4-8L / min, and keep the temperature for 1-1.5h; The third stage of sintering: Finally, the temperature is raised to 1200-1300℃ at a heating rate of 4-7℃ / min and kept at this temperature for 2-4h; Cooling stage: After sintering, the rotor is cooled to room temperature at a rate of 4-6°C / min, and hydrogen is continuously introduced at a rate of 3-5L / min during the cooling process.

[0006] Preferably, the surface treatment includes pre-cleaning, surface activation, coating treatment, curing treatment and quality inspection and repair; Pre-cleaning: First use a compressed air spray gun to blow away the impurities on the surface of the magnetic rotor, then put the magnetic rotor into an ultrasonic cleaner and add 75% ethanol solution. The ethanol solution should cover the magnetic rotor. After soaking for 3-4 minutes, start the ultrasonic cleaner to remove impurities on the rotor surface through high-frequency vibration. The ultrasonic frequency is 30-40kHz and the power density is 0.4-0.5W / cm². After 5-10 minutes of treatment, rinse with clean water and dry in a low-temperature drying oven at a temperature of 40-50℃ for 1-3 hours. Surface activation: put the cleaned magnetic rotor into the activation solution and etch it with ultrasonic vibration. The ultrasonic frequency is 20-30kHz and the power density is 0.4-0.6W / cm². Take out the rotor after 10-15s, rinse it with plenty of water, and then dry it in a low-temperature drying oven at 40-60℃ for 1-3h. Coating treatment: Use electrostatic spraying technology to coat the epoxy resin on the surface of the magnetic rotor, with a coating thickness of 0.1-0.2mm; Curing treatment: Place the coated magnetic rotor in the curing furnace, close the furnace door, set the initial temperature to 40-45℃, and keep it for 20-30min, then increase the temperature to 80-90℃ at a heating rate of 5-10℃ / min, and keep it at 80-90℃ for 30-50min, then increase the temperature to 120-130℃ at a heating rate of 3-5℃ / min, and keep it at 120-130℃ for 1-2h. After curing, turn off the heating device of the curing furnace, let the magnetic rotor cool naturally in the furnace, and open the furnace door to take out the magnetic rotor when the temperature in the furnace drops to 40-45℃, where the cooling rate is 3-6℃ / min; Quality inspection and repair: Observe the epoxy resin coating of the magnetic rotor with the naked eye to check for defects such as bubbles, cracks, flow marks, and exposed bottom. Use a thickness gauge to measure the thickness of the epoxy resin coating, screen out rotors with unqualified coating thickness, and repair the unqualified rotors according to the coating treatment and curing treatment steps.

[0007] Preferably, the crushing process includes premixing, pre-burning and grinding; Premixing: Add iron oxide, barium oxide, rare earth elements, silicon carbide fiber, titanium dioxide, silicon dioxide and calcium carbonate into a planetary ball mill in sequence to mix the raw materials at a stirring speed of 40-50 rpm for 4-6 hours to form a mixture; Pre-sintering treatment: put the mixed material into a pre-sintering furnace, introduce argon gas into the pre-sintering furnace, and pre-sinter for 3-5 hours at a temperature of 1240-1260°C to generate hexagonal ferrite grains, wherein the pushing plate speed is 30-40 minutes / plate, and the atmosphere flow rate is 0.5-1L / min; Grinding and powdering: Put the pre-sintered grains into a ball mill, add water into the ball mill, and ball mill at a speed of 28-32rpm for 12-16h to obtain permanent magnet ferrite magnetic powder.

[0008] Preferably, the molding process includes pre-treatment and injection molding; Pretreatment: Dry the obtained permanent ferrite magnetic powder in a vacuum drying oven at 60-80°C for 2-4 hours, then screen the powder to ensure that the particle size of the powder is 0.5-1.2 μm, then add plasticizer, lubricant and binder to the permanent ferrite magnetic powder, and stir at 80-120 rpm for 10-40 minutes to obtain a mixture; Injection molding: first preheat the mold in the injection machine at a preheating temperature of 80-100°C, then add the mixture into the barrel of the injection machine for plasticization, wherein the plasticization temperature is 120-140°C, the screw speed is 40-60rpm, after 0.5-3min, the screw injects the plasticized melt into the preheated mold cavity through the nozzle, the injection pressure is 60-120MPa, the injection speed is 20-40mm / s, after the melt is injected into the mold cavity, immediately introduce cooling air to cool the mold, so that the melt is quickly solidified and formed in the mold, wherein the cooling time is 20-40s, when the magnet is cooled to 40-60°C, open the mold, and push the molded magnet out of the mold through the ejection mechanism to obtain a magnetic rotor.

[0009] Preferably, the processing and magnetization include mechanical processing, magnetization and post-magnetization processing and testing; Mechanical processing: The rotor is ground using an 80-mesh grinding wheel, where the rotation speed of the grinding wheel is 2000-2500r / min and the feed speed is 0.02-0.04mm / r; Magnetization: Place the rotor in the magnetization fixture of the pulse magnetizer and start the magnetizer for magnetization, where the magnetic field strength is 300-500kA / m and the pulse width is 4-8ms.

[0010] Preferably, the post-magnetization processing and detection includes demagnetization inspection and magnetic property stabilization processing; Demagnetization inspection: Use a Gauss meter to measure the magnetic field strength of different parts of the magnetized rotor to determine whether the magnetic field strength of the rotor is uniform, and re-magnetize the rotor that fails to meet the magnetization requirements; Magnetic property stabilization treatment: The inspected magnetic rotor is placed in an environment of 50-60℃ for aging treatment for 2-6h, then the rotor is placed in an environment of -5℃~20℃ for cooling for 3-4h, and the aging treatment and cooling treatment are cycled 3-4 times.

[0011] Preferably, the performance test includes magnetic performance test, mechanical performance test and appearance quality test; Magnetic performance testing: Use a Gauss meter to measure the residual magnetism of the magnetic rotor, use a pulse magnetometer to detect the coercive force of the magnetic rotor, and use a special magnetic material measurement system to detect the magnetic energy product; Mechanical property testing: Use Rockwell hardness tester to test the hardness of permanent ferrite magnetic rotor to obtain Rockwell hardness, use pressure testing machine to test compressive strength, and use special bending test device to test the flexural strength of the rotor; Appearance quality inspection: Use a roughness meter to detect the surface roughness of the magnetic rotor.

[0012] Preferably, the mass ratio of the iron oxide, barium oxide, rare earth element, silicon carbide fiber, titanium dioxide, silicon dioxide, calcium carbonate, plasticizer, lubricant and binder is (60-75):(24-28):(0-3.5):(0-4):(0.5-1.5):(0.1-0.5):(0.2-1):(2-5):(1-3):(5-7).

[0013] Preferably, the particle size of the iron oxide is 1-2 μm, the purity of the iron oxide is 96% to 100%, the rare earth element is one of lanthanum and cerium, and the binder is one of nylon and polyphenylene sulfide.

[0014] Preferably, the activation solution is one of 10% to 20% nitric acid solution, 5% to 15% sodium hydroxide solution and 5% to 10% citric acid solution.

[0015] Compared with the prior art, the present invention has the following beneficial effects: 1. The present invention improves the magnetic properties by adding rare earth elements during preparation, changing the microstructure and magnetocrystalline anisotropy of the magnet through doping modification. The addition of rare earth elements can change the crystal structure and magnetic domain structure of the magnet, making the magnetic properties more stable when the temperature changes. The addition of rare earth elements can refine the grains, improve magnetic properties such as coercive force and remanence, and adopt a staged sintering process to control the heating rate and holding time at different temperature stages, which can make the grain structure inside the material more dense and uniform, help fix the magnetic domain structure, reduce the influence of temperature on remanence, so that the magnetism of the magnetic rotor prepared subsequently will not change significantly due to temperature changes, and effectively improve the temperature stability of the magnet.

[0016] 2. The present invention uses epoxy resin material to coat the surface of the magnetic rotor to form a protective film, which can not only improve the surface hardness, but also prevent the external environment from corroding the magnet, thereby indirectly improving the mechanical strength. The magnetic rotor is treated by magnetizing first and then surface treating, which can protect the magnetic properties to a certain extent. In order to ensure the quality of the coating, the magnetic rotor is surface activated and coated with electrostatic spraying technology to reduce the interference between the magnetizing operation and the surface treatment, thereby improving the mechanical strength of the prepared permanent magnet ferrite magnetic rotor and extending the service life of the rotor.

[0017] 3. The present invention improves the pre-firing process, increases the pre-firing temperature and prolongs the pre-firing time, so that the raw materials can better form a ferrite phase during the pre-firing process, promote grain growth and improve the magnetic domain structure, thereby improving the density and magnetic properties of the magnet.

[0018] 4. The present invention introduces fibers and undergoes a sintering process to make the permanent magnet ferrite matrix composite material structure dense, improve its fracture toughness and impact strength, and at the same time help to improve the thermal stability of the material to a certain extent. The introduction of titanium dioxide and silicon dioxide adjusts the grain boundary characteristics, improves the sintering performance, makes the grain growth more uniform, reduces the generation of defects such as pores, and has a certain regulating effect on the final magnetic properties and microstructure, thereby improving the overall performance of the magnetic rotor to a certain extent. DETAILED DESCRIPTION

[0019] The technical solutions in the embodiments of the present invention are described clearly and completely. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0020] The present invention provides a preparation process of a permanent ferrite magnetic rotor: the preparation steps are as follows: Step S1: Raw material preparation: iron oxide, barium oxide, rare earth elements, silicon carbide fiber, titanium dioxide, silicon dioxide, calcium carbonate, plasticizer, lubricant and binder, Step S2: Crushing treatment: iron oxide, barium oxide, rare earth elements, silicon carbide fiber, titanium dioxide, silicon dioxide and calcium carbonate are sequentially added into a planetary ball mill for raw material mixing, the stirring speed is 45rpm, the mixing is performed for 4h to form a mixture, and then the mixture is placed into a pre-sintering furnace, and argon gas is introduced into the pre-sintering furnace, and the mixture is pre-sintered at a temperature of 1240°C for 5h to generate hexagonal ferrite grains, wherein the push plate speed is 35 minutes / plate, and the atmosphere flow rate is 0.6L / min, and then the pre-sintered grains are placed into a ball mill, and water is added to the ball mill, and the mixture is ball-milled at a speed of 30rpm for 14h to obtain permanent ferrite magnetic powder, wherein the particle size of the iron oxide is 1μm and the purity is 98%; Step S3: Molding process: The obtained permanent ferrite magnetic powder is dried in a vacuum drying oven and dried at 60°C for 4 hours. The powder is then screened to ensure that the particle size of the powder is 1 μm. Plasticizer, lubricant and binder are then added to the permanent ferrite magnetic powder, and stirred at 100 rpm for 25 minutes to obtain a mixture. The mold in the injection molding machine is then preheated at 80°C. The mixture is then added to the barrel of the injection molding machine for plasticization at a plasticizing temperature of 130°C and a screw speed of 60 rpm. After 1.5 minutes, the screw injects the plasticized melt into the preheated mold cavity through a nozzle. In the process, the injection pressure is 80 MPa, the injection speed is 30 mm / s, and after the melt is injected into the mold cavity, cooling air is immediately introduced to cool the mold so that the melt can be quickly solidified in the mold. The cooling time is 30 seconds. When the magnet is cooled to 40°C, the mold is opened, and the molded magnet is pushed out of the mold by the ejection mechanism to obtain a magnetic rotor. The mass ratios of iron oxide, barium oxide, rare earth elements, silicon carbide fiber, titanium dioxide, silicon dioxide, calcium carbonate, plasticizer, lubricant and binder are (60-75): (24-28): (0-3.5): (0-4): (0.5-1.5): (0.1-0.5): 0.8:3:2:5; Step S4: Sintering process: first inspect the green body of the formed magnetic rotor, remove the rotor with surface defects, then put the qualified rotor into the sintering furnace, and introduce oxygen into the furnace in advance, the atmosphere flow rate is 0.2L / min, and heat it at a heating rate of 2℃ / min after 6min. When the temperature rises to 460℃, stop heating and keep it warm for 60min, then increase the temperature to 960℃ at a heating rate of 8℃ / min, and introduce hydrogen into it, the atmosphere flow rate is 6L / min, keep it warm for 1h, finally increase the temperature to 1200℃ at a heating rate of 6℃ / min, and keep it warm for 3h, then cool the rotor after sintering, cool the temperature to room temperature at a rate of 5℃ / min, and continue to introduce hydrogen at a rate of 4L / min during the cooling process; Step S5: processing and magnetization: grinding the rotor with an 80-mesh grinding wheel, wherein the rotation speed of the grinding wheel is 2400r / min and the feed speed is 0.03mm / r, then placing the rotor in the magnetization fixture of the pulse magnetizer, starting the magnetizer for magnetization, wherein the magnetic field strength is 400kA / m and the pulse width is 6ms, after the magnetization is completed, using a Gauss meter to measure the magnetic field strength of different parts of the magnetized rotor to determine whether the magnetic field strength of the rotor is uniform, and re-magnetizing the rotor that fails the magnetization, and placing the inspected magnetic rotor in an environment of 55°C for aging treatment for 5h, and then placing the rotor in an environment of 10°C for cooling for 3h, and cyclically performing the aging treatment and cooling treatment for 3 times; Step S6: Surface treatment: First, use a compressed air spray gun to blow away impurities on the surface of the magnetic rotor, then put the magnetic rotor into an ultrasonic cleaning machine, and add 75% ethanol solution, the ethanol solution covers the magnetic rotor, soak for 3 minutes, start the ultrasonic cleaning machine to remove impurities on the rotor surface through high-frequency vibration, wherein the ultrasonic frequency is 40kHz, the power density is 0.4W / cm², after 10 minutes of treatment, rinse with clean water, and use a low-temperature drying oven to dry at 45°C for 2 hours, then put the cleaned magnetic rotor into the activation solution, and etch the magnetic rotor with ultrasonic vibration, the ultrasonic frequency is 30kHz, the power density is 0.5W / cm², take out the rotor after 10 seconds, then rinse with a large amount of clean water, and then use a low-temperature drying oven to dry at 50°C for 2 hours, then use electrostatic spraying technology to coat the epoxy resin On the surface of the magnetic rotor, the coating thickness is 0.1mm. The coated magnetic rotor is then placed in a curing furnace, the furnace door is closed, the initial temperature is set to 40°C, and after maintaining for 30 minutes, the temperature is increased to 85°C at a heating rate of 5°C / min, and maintained at 85°C for 40 minutes, then the temperature is increased to 125°C at a heating rate of 5°C / min, and maintained at 125°C for 2 hours. After the curing is completed, the heating device of the curing furnace is turned off, and the magnetic rotor is allowed to cool naturally in the furnace. When the temperature in the furnace drops to 40°C, the furnace door is opened to take out the magnetic rotor, and the cooling rate is 5°C / min. The epoxy resin coating of the magnetic rotor is observed with the naked eye to check for defects such as bubbles, cracks, flow marks, and bottom exposure, and the thickness of the epoxy resin coating is measured using a thickness gauge to screen out rotors with unqualified coating thickness, and the unqualified rotors are repaired according to the steps of coating treatment and curing treatment.

[0021] Further, the value of step S3 is changed, and steps S1-2 and S4-6 are performed to perform magnetic property tests, mechanical property tests and appearance quality tests on the prepared permanent magnet ferrite magnetic rotor. The residual magnetism temperature coefficient also needs to be tested. The sample is placed in a magnetic property measuring device, and its initial residual magnetism Br1 is measured at room temperature. Then, the sample is placed in a temperature control device, and the temperature is increased to 100°C at a heating rate of 5°C / min and maintained for 40 minutes. Then, the residual magnetism Br2 is measured again at this temperature, and the residual magnetism temperature coefficient is calculated according to the formula.

[0022] Embodiment 1: Step S3: Molding process: The obtained permanent ferrite magnetic powder is dried in a vacuum drying oven and dried at 60°C for 4 hours. Then the powder is screened to ensure that the particle size of the powder is 1 μm. Then, a plasticizer, a lubricant, and a binder are added to the permanent ferrite magnetic powder, and stirred at a speed of 100 rpm for 25 minutes to obtain a mixture. Then, the mold in the injection molding machine is preheated at a preheating temperature of 80°C. Then, the mixture is added to the barrel of the injection molding machine for plasticization, wherein the plasticization temperature is 130°C and the screw speed is 60 rpm. After 1.5 minutes, the screw will plasticize the melt. The melt is injected into the preheated mold cavity through a nozzle, the injection pressure is 80 MPa, and the injection speed is 30 mm / s. After the melt is injected into the mold cavity, cooling air is immediately introduced to cool the mold so that the melt can be quickly solidified in the mold. The cooling time is 30 s. When the magnet is cooled to 40°C, the mold is opened and the molded magnet is pushed out of the mold by an ejection mechanism to obtain a magnetic rotor. The mass ratio of iron oxide, barium oxide, rare earth elements, silicon carbide fiber, titanium dioxide, silicon dioxide, calcium carbonate, plasticizer, lubricant and binder is 70:25:0:0:0.5:0.1:0.8:3:2:5.

[0023] Furthermore, the remanence was measured to be 0.28T, the remanence temperature coefficient was 13.2% / ℃, the coercive force was 189kA / m, the magnetic energy product was 18kJ / m³, the Rockwell hardness was 47, the compressive strength was 73MPa, the flexural strength was 36MPa, and the surface roughness was 1.7μm.

[0024] Embodiment 2: Step S3: Molding process: The obtained permanent ferrite magnetic powder is dried in a vacuum drying oven and dried at 60°C for 4 hours. Then the powder is screened to ensure that the particle size of the powder is 1 μm. Then, a plasticizer, a lubricant, and a binder are added to the permanent ferrite magnetic powder, and stirred at a speed of 100 rpm for 25 minutes to obtain a mixture. Then, the mold in the injection molding machine is preheated at a preheating temperature of 80°C. Then, the mixture is added to the barrel of the injection molding machine for plasticization, wherein the plasticization temperature is 130°C and the screw speed is 60 rpm. After 1.5 minutes, the screw will plasticize the melt. The melt is injected into the preheated mold cavity through a nozzle, the injection pressure is 80 MPa, and the injection speed is 30 mm / s. After the melt is injected into the mold cavity, cooling air is immediately introduced to cool the mold so that the melt can be quickly solidified in the mold. The cooling time is 30 s. When the magnet is cooled to 40°C, the mold is opened and the molded magnet is pushed out of the mold by an ejection mechanism to obtain a magnetic rotor. The mass ratio of iron oxide, barium oxide, rare earth elements, silicon carbide fiber, titanium dioxide, silicon dioxide, calcium carbonate, plasticizer, lubricant and binder is 70:25:1:1:0.8:0.2:0.8:3:2:5.

[0025] Furthermore, the remanence was measured to be 0.34T, the remanence temperature coefficient was 11.6% / ℃, the coercive force was 203kA / m, the magnetic energy product was 22kJ / m³, the Rockwell hardness was 53, the compressive strength was 87MPa, the flexural strength was 41MPa, and the surface roughness was 1.5μm.

[0026] Embodiment three: Step S3: Molding process: The obtained permanent ferrite magnetic powder is dried in a vacuum drying oven and dried at 60°C for 4 hours. Then the powder is screened to ensure that the particle size of the powder is 1 μm. Then, a plasticizer, a lubricant, and a binder are added to the permanent ferrite magnetic powder, and stirred at a speed of 100 rpm for 25 minutes to obtain a mixture. Then, the mold in the injection molding machine is preheated at a preheating temperature of 80°C. Then, the mixture is added to the barrel of the injection molding machine for plasticization, wherein the plasticization temperature is 130°C and the screw speed is 60 rpm. After 1.5 minutes, the screw will plasticize the melt. The melt is injected into the preheated mold cavity through a nozzle, the injection pressure is 80 MPa, and the injection speed is 30 mm / s. After the melt is injected into the mold cavity, cooling air is immediately introduced to cool the mold so that the melt can be quickly solidified in the mold. The cooling time is 30 s. When the magnet is cooled to 40°C, the mold is opened and the molded magnet is pushed out of the mold by the pushing mechanism to obtain a magnetic rotor. The mass ratio of iron oxide, barium oxide, rare earth elements, silicon carbide fiber, titanium dioxide, silicon dioxide, calcium carbonate, plasticizer, lubricant and binder is 70:25:2.5:2:1:0.2:0.8:3:2:5.

[0027] Furthermore, the remanence was measured to be 0.46T, the remanence temperature coefficient was 10.2% / ℃, the coercive force was 237kA / m, the magnetic energy product was 29kJ / m³, the Rockwell hardness was 59, the compressive strength was 98MPa, the flexural strength was 48MPa, and the surface roughness was 1.1μm.

[0028] Embodiment 4: Step S3: Molding process: The obtained permanent ferrite magnetic powder is dried in a vacuum drying oven at 60°C for 4 hours, and then the powder is screened to ensure that the particle size of the powder is 1 μm, and then a plasticizer, a lubricant, and a binder are added to the permanent ferrite magnetic powder, and stirred at a speed of 100 rpm for 25 minutes to obtain a mixture, and then the mold in the injection molding machine is preheated at a preheating temperature of 80°C, and then the mixture is added to the barrel of the injection molding machine for plasticization, wherein the plasticization temperature is 130°C, the screw speed is 60 rpm, and after 1.5 minutes, the screw will plasticize the plasticized The melt is injected into the preheated mold cavity through a nozzle, the injection pressure is 80 MPa, and the injection speed is 30 mm / s. After the melt is injected into the mold cavity, cooling air is immediately introduced to cool the mold so that the melt can be quickly solidified in the mold. The cooling time is 30 seconds. When the magnet is cooled to 40°C, the mold is opened and the molded magnet is pushed out of the mold by an ejection mechanism to obtain a magnetic rotor. The mass ratio of iron oxide, barium oxide, rare earth elements, silicon carbide fiber, titanium dioxide, silicon dioxide, calcium carbonate, plasticizer, lubricant and binder is 70:25:3:3:1:0.4:0.8:3:2:5.

[0029] Furthermore, the remanence was measured to be 0.42T, the remanence temperature coefficient was 10.9% / ℃, the coercive force was 228kA / m, the magnetic energy product was 25kJ / m³, the Rockwell hardness was 57, the compressive strength was 92MPa, the flexural strength was 46MPa, and the surface roughness was 1.2μm.

[0030] Embodiment five: Step S3: Molding process: The obtained permanent ferrite magnetic powder is dried in a vacuum drying oven and dried at 60°C for 4 hours. Then the powder is screened to ensure that the particle size of the powder is 1 μm. Then, a plasticizer, a lubricant, and a binder are added to the permanent ferrite magnetic powder, and stirred at a speed of 100 rpm for 25 minutes to obtain a mixture. Then, the mold in the injection molding machine is preheated at a preheating temperature of 80°C. Then, the mixture is added to the barrel of the injection molding machine for plasticization, wherein the plasticization temperature is 130°C and the screw speed is 60 rpm. After 1.5 minutes, the screw melts the plasticized melt. It is injected into the preheated mold cavity through a nozzle, the injection pressure is 80MPa, the injection speed is 30mm / s, and after the melt is injected into the mold cavity, cooling air is immediately introduced to cool the mold so that the melt can be quickly solidified in the mold. The cooling time is 30s. When the magnet is cooled to 40°C, the mold is opened and the molded magnet is pushed out of the mold by the pushing mechanism to obtain a magnetic rotor. The mass ratio of iron oxide, barium oxide, rare earth elements, silicon carbide fiber, titanium dioxide, silicon dioxide, calcium carbonate, plasticizer, lubricant and binder is 70:25:3:3.5:1.2:0.4:0.8:3:2:5.

[0031] Furthermore, the remanence was measured to be 0.37T, the remanence temperature coefficient was 11.7% / ℃, the coercive force was 215kA / m, the magnetic energy product was 21kJ / m³, the Rockwell hardness was 52, the compressive strength was 85MPa, the flexural strength was 43MPa, and the surface roughness was 1.6μm.

[0032] The performance test results of the permanent ferrite magnetic rotor are as follows:

[0033] It will be apparent to those skilled in the art that the present invention is not limited to the details of the exemplary embodiments described above and that the present invention can be implemented in other specific forms without departing from the spirit or essential features of the present invention. Therefore, the embodiments should be considered exemplary and non-restrictive in all respects, and the scope of the present invention is defined by the appended claims rather than the above description, and it is intended that all changes falling within the meaning and scope of the equivalent elements of the claims be included in the present invention.

Claims

1. A process for preparing a permanent ferrite magnetic rotor, characterized in that: It includes raw material preparation, crushing, molding, sintering, processing and magnetization, surface treatment and performance testing. The crushing mixes large particles of raw materials together and grinds them into permanent ferrite magnetic powder. The molding adopts injection molding to press the powder into a rotor. The sintering adopts a segmented sintering process to perform high-temperature sintering on the formed green body to form a permanent ferrite phase with stable magnetic properties. The processing and magnetization perform mechanical processing and magnetization on the sintered rotor. The surface treatment is used to coat a protective film on the surface of the magnetic rotor. The performance test is carried out according to the standard documents of GB / T12796.1-2012 and GB / T3217-2013 to screen out products with unqualified quality. The raw materials include iron oxide, barium oxide, rare earth elements, silicon carbide fiber, titanium dioxide, silicon dioxide, calcium carbonate, plasticizer, lubricant and binder; The sintering process includes sintering pre-treatment, first stage sintering, second stage sintering, third stage sintering and cooling stages; Pre-sintering treatment: Check the green body of the formed magnetic rotor, remove the rotors with surface defects, and then put the qualified rotors into the sintering furnace, and introduce oxygen into the furnace in advance, with an atmosphere flow rate of 0.2-0.3L / min; The first stage of sintering: After 5-10 minutes, heat at a heating rate of 2-4℃ / min. When the temperature reaches 450-550℃, stop heating and keep warm for 40-80 minutes. Second stage sintering: then raise the temperature to 950-1050°C at a heating rate of 6-9°C / min, introduce hydrogen into the sintered steel sheet at an atmosphere flow rate of 4-8L / min, and keep the temperature for 1-1.5h; The third stage of sintering: Finally, the temperature is raised to 1200-1300℃ at a heating rate of 4-7℃ / min and kept at this temperature for 2-4h; Cooling stage: After sintering, the rotor is cooled to room temperature at a rate of 4-6°C / min, and hydrogen is continuously introduced at a rate of 3-5L / min during the cooling process.

2. The process for preparing a permanent magnet ferrite magnetic rotor according to claim 1, characterized in that: The surface treatment includes pre-cleaning, surface activation, coating treatment, curing treatment and quality inspection and repair; Pre-cleaning: First use a compressed air spray gun to blow away the impurities on the surface of the magnetic rotor, then put the magnetic rotor into an ultrasonic cleaner and add 75% ethanol solution. The ethanol solution should cover the magnetic rotor. After soaking for 3-4 minutes, start the ultrasonic cleaner to remove impurities on the rotor surface through high-frequency vibration. The ultrasonic frequency is 30-40kHz and the power density is 0.4-0.5W / cm². After 5-10 minutes of treatment, rinse with clean water and dry in a low-temperature drying oven at a temperature of 40-50℃ for 1-3 hours. Surface activation: put the cleaned magnetic rotor into the activation solution and etch it with ultrasonic vibration. The ultrasonic frequency is 20-30kHz and the power density is 0.4-0.6W / cm². Take out the rotor after 10-15s, rinse it with plenty of water, and then dry it in a low-temperature drying oven at 40-60℃ for 1-3h. Coating treatment: Use electrostatic spraying technology to coat the epoxy resin on the surface of the magnetic rotor, with a coating thickness of 0.1-0.2mm; Curing treatment: Place the coated magnetic rotor in the curing furnace, close the furnace door, set the initial temperature to 40-45℃, and keep it for 20-30min, then increase the temperature to 80-90℃ at a heating rate of 5-10℃ / min, and keep it at 80-90℃ for 30-50min, then increase the temperature to 120-130℃ at a heating rate of 3-5℃ / min, and keep it at 120-130℃ for 1-2h. After curing, turn off the heating device of the curing furnace, let the magnetic rotor cool naturally in the furnace, and open the furnace door to take out the magnetic rotor when the temperature in the furnace drops to 40-45℃, where the cooling rate is 3-6℃ / min; Quality inspection and repair: Observe the epoxy resin coating of the magnetic rotor with the naked eye to check for defects such as bubbles, cracks, flow marks, and exposed bottom. Use a thickness gauge to measure the thickness of the epoxy resin coating, screen out rotors with unqualified coating thickness, and repair the unqualified rotors according to the coating treatment and curing treatment steps.

3. The process for preparing a permanent magnet ferrite magnetic rotor according to claim 1, characterized in that: The crushing process includes premixing, pre-burning and grinding; Premixing: Add iron oxide, barium oxide, rare earth elements, silicon carbide fiber, titanium dioxide, silicon dioxide and calcium carbonate into a planetary ball mill in sequence to mix the raw materials at a stirring speed of 40-50 rpm for 4-6 hours to form a mixture; Pre-sintering treatment: put the mixed material into a pre-sintering furnace, introduce argon gas into the pre-sintering furnace, and pre-sinter for 3-5 hours at a temperature of 1240-1260°C to generate hexagonal ferrite grains, wherein the pushing plate speed is 30-40 minutes / plate, and the atmosphere flow rate is 0.5-1L / min; Grinding and powdering: Put the pre-sintered grains into a ball mill, add water into the ball mill, and ball mill at a speed of 28-32rpm for 12-16h to obtain permanent magnet ferrite magnetic powder.

4. The process for preparing a permanent magnet ferrite magnetic rotor according to claim 1, characterized in that: The molding process includes pre-treatment and injection molding; Pretreatment: Dry the obtained permanent ferrite magnetic powder in a vacuum drying oven at 60-80°C for 2-4 hours, then screen the powder to ensure that the particle size of the powder is 0.5-1.2 μm, then add plasticizer, lubricant and binder to the permanent ferrite magnetic powder, and stir at 80-120 rpm for 10-40 minutes to obtain a mixture; Injection molding: first preheat the mold in the injection machine at a preheating temperature of 80-100°C, then add the mixture into the barrel of the injection machine for plasticization, wherein the plasticization temperature is 120-140°C, the screw speed is 40-60rpm, after 0.5-3min, the screw injects the plasticized melt into the preheated mold cavity through the nozzle, the injection pressure is 60-120MPa, the injection speed is 20-40mm / s, after the melt is injected into the mold cavity, immediately introduce cooling air to cool the mold, so that the melt is quickly solidified and formed in the mold, wherein the cooling time is 20-40s, when the magnet is cooled to 40-60°C, open the mold, and push the molded magnet out of the mold through the ejection mechanism to obtain a magnetic rotor.

5. The process for preparing a permanent magnet ferrite magnetic rotor according to claim 1, characterized in that: The processing and magnetization include mechanical processing, magnetization and post-magnetization processing and testing; Mechanical processing: The rotor is ground using an 80-mesh grinding wheel, where the rotation speed of the grinding wheel is 2000-2500r / min and the feed speed is 0.02-0.04mm / r; Magnetization: Place the rotor in the magnetization fixture of the pulse magnetizer and start the magnetizer for magnetization, where the magnetic field strength is 300-500kA / m and the pulse width is 4-8ms.

6. The process for preparing a permanent magnet ferrite magnetic rotor according to claim 5, characterized in that: The post-magnetization processing and detection includes demagnetization inspection and magnetic property stabilization processing; Demagnetization inspection: Use a Gauss meter to measure the magnetic field strength of different parts of the magnetized rotor to determine whether the magnetic field strength of the rotor is uniform, and re-magnetize the rotor that fails to meet the magnetization requirements; Magnetic property stabilization treatment: The inspected magnetic rotor is placed in an environment of 50-60℃ for aging treatment for 2-6h, then the rotor is placed in an environment of -5℃~20℃ for cooling for 3-4h, and the aging treatment and cooling treatment are cycled 3-4 times.

7. The process for preparing a permanent ferrite magnetic rotor according to claim 1, characterized in that: The performance test includes magnetic performance test, mechanical performance test and appearance quality test; Magnetic performance testing: Use a Gauss meter to measure the residual magnetism of the magnetic rotor, use a pulse magnetometer to detect the coercive force of the magnetic rotor, and use a special magnetic material measurement system to detect the magnetic energy product; Mechanical property testing: Use Rockwell hardness tester to test the hardness of permanent ferrite magnetic rotor to obtain Rockwell hardness, use pressure testing machine to test compressive strength, and use special bending test device to test the flexural strength of the rotor; Appearance quality inspection: Use a roughness meter to detect the surface roughness of the magnetic rotor.

8. The process for preparing a permanent ferrite magnetic rotor according to claim 1, characterized in that: The mass ratio of the iron oxide, barium oxide, rare earth element, silicon carbide fiber, titanium dioxide, silicon dioxide, calcium carbonate, plasticizer, lubricant and binder is (60-75): (24-28): (0-3.5): (0-4): (0.5-1.5): (0.1-0.5): (0.2-1): (2-5): (1-3): (5-7).

9. The process for preparing a permanent ferrite magnetic rotor according to claim 1, characterized in that: The particle size of the iron oxide is 1-2 μm, the purity of the iron oxide is 96% to 100%, the rare earth element is one of lanthanum and cerium, and the binder is one of nylon and polyphenylene sulfide.

10. The process for preparing a permanent ferrite magnetic rotor according to claim 2, characterized in that: The activation solution is one of 10% to 20% nitric acid solution, 5% to 15% sodium hydroxide solution and 5% to 10% citric acid solution.

Citation Information

Patent Citations

  • A method for fabricating a permanent magnet rotor assembly

    CN110149034B

  • A high-performance injection-molded and sintered permanent magnet ferrite magnet and its preparation method

    CN111362681B

  • A high-strength stainless steel rotor and its preparation method

    CN111471940B